Penerapan Teknik “ Mind Mapping” dalam Pembelajaran Reading untuk Meningkatkan Kemampuan Literasi dan Berpikir Kritis Siswa - Saputra, Ari; Sahyatini, Sahyatini (Lembaga Yasin AlSys, 2022)
This research aimed at finding the effectiveness of mind mapping technique in teaching reading to improve the literacy skill and students’ critical thinking for the tenth grade of SMAN 3 Selong. The stages in this research used lesson study method where there are three things to do, namely the plan, do, and see stages. There are 2 cycles that are carried out in the class, at the first circle is teaching narrative material in class X IPA 1 while the redesigned learning design is at grade X IPA 2 with recount text. The results of the process carried out during the two cycles were an increase in student literacy where the application of the Mind Mapping Technique made it easier for students to understand and simplify material and information in learning to read. class and share about the experience of managing the class. And also this partnership program can be collaborated with various other innovative learning methods and models. It is hoped that this program can be maintained in schools